Hall sensor-based speed control of a 3-phase permanent-magnet synchronous motor using a field-oriented algorithm - Abidaoun H. Shallal; Saad Abdulmajeed Salman; Ahmad H. Sabry (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
To achieve optimum torque per amp, we retain the angle of the stator-current-vector with respect to the rotor-flux at 90 degrees, rather than controlling the amplitude of the stator-current-vector. Without or with the load torque, the proportional integral (PI) controller produced better results in the speed control loop. A controller is required to maintain a consistent speed and improve system performance as the load changes. This work develops an auto-tuning PI speed controller for 3-phase permanent-magn et synchronous motors using field oriented algorithm. The 3-phase voltage from the grid is converted to DC through a transformer and a grid-side rectifier. The DC voltage is converted back into AC through a machine-side inverter, which drives the motor with time-varying loud. The objective of field oriented control (FOC) in this work is to control the semiconductor switches in the machine-side power inverter to achieve the desired torque and flux. The stator-currents are measured and fed into the flux observer to obtain the direct-quadrature-zero (DQ-axis) current, the rotor magn etizing current, and the angle of the synchronously rotating reference frame. The results show that the motor's speed response has an earlier transient response and a less steady-state inaccuracy after tuning the controllers during acceleration and torque load adjustments.